Revisited Anterolateral Thigh Free Flaps For Reconstructive Microsurgery : One Year Evaluation - Atmodiwirjo, Parintosa; Handayani, Siti; Djaprie, Shelly Madona (Lingkar Studi Bedah Plastik Foundation, 2012)
Extensive soft tissue defects present a dif!cult problem to the plastic surgeon as they are usually associated with exposed important structures such as vessels, nerves, tendons, joint cavity or bone. Reconstruction of soft tissue defects have a wide range of therapeutic options. We reconstructed soft tissue defect in many areas using free anterolateral thigh flap (ALTF). From Februari 2009 - 2010, 9 cases of soft tissue defects in the face, neck, leg and foot of various etiologic factors were admitted to the plastic and reconstructive surgery unit, Cipto Mangunkusumo general hospital. Trauma is the commonest cause of soft tissue defects of the lower extremity, followed by tumours. The cruris was the commonest site (4 cases, 44,4%). Flap success rate was 66,67 %. Failure was reported 1 cases in this study due to vein compromise. In our hospital, we are quite familiar with Anterolateral thigh flap (ALTF) even though the case is limited. Anterolateral thigh flap (ALTF) is used for reconstruction of various simple and complex soft tissue defects, for big and small defects with cavity (orbita).